MORAL VALUES IN FINDING NEMO MOVIE - Cut Faizah; Nyak Mutia Ismail (Linguistics and Literature Students' Journal, 2023)
The focus of the study pertains to the narrative structure of the plot in the film Finding Nemo. The plot of a narrative is comprised of a series of occurrences that are interconnected through the principle of causation, whereby each event influences the subsequent one. Besides, this study also sought to find the moral values implied in the movie. The methodology used was descriptive qualitative, where the movie Finding Nemo 100 minutes in length as the source of data. The data collection was carried out through documentation steps, and the data analysis used was interactive analysis involving data condensation, data display, and data verification. The results indicate that the plot of the movie is condensed consisting of the exposition, conflict, rising action, climax, falling action, and resolution. Then, the moral values that lie in the movie are parental bonding, compliance, perseverance, and collaboration.Conclusively, Finding Nemo is a good movie for children to watch as a source of education. The movie teaches important lessons about the importance of family, perseverance, and overcoming challenges via collaborative means.Keywords: Artwork, film studies, literature, moral values, movie plots